1964
DOI: 10.1121/1.1918927
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Backscattering of Sound from the Ocean Bottom

Abstract: Data obtained from the measurement of backscattering of sound from the ocean bottom at 16 locations around the coast of the United States of America are presented. Data are given as a function of grazing angle and frequency for mud, sand, and gravel. The range of frequency was 12.5 to 290 kc/sec and the range of grazing angle was 1.0 ø to 90 ø. Backscattering increased with grazing angle according to the sin and sin", depending on the value of angle and the type of sediment. Backscattering increased with frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

1969
1969
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(22 citation statements)
references
References 0 publications
2
18
0
2
Order By: Relevance
“…12, we compare the measured SB at 30 with the grain size as derived from the corresponding North Sea grabs for sediments without gravel (practically, this means 1%). Also given in the figure are measurements that have been published in [6], [8], [21], and [22]. Our data and the data from literature are in good agreement and they show that there is virtually no relation between scattering strength and grain size [6].…”
Section: A Comparison Of Measured With Literaturesupporting
confidence: 77%
See 1 more Smart Citation
“…12, we compare the measured SB at 30 with the grain size as derived from the corresponding North Sea grabs for sediments without gravel (practically, this means 1%). Also given in the figure are measurements that have been published in [6], [8], [21], and [22]. Our data and the data from literature are in good agreement and they show that there is virtually no relation between scattering strength and grain size [6].…”
Section: A Comparison Of Measured With Literaturesupporting
confidence: 77%
“…We estimate the error in applying Lambert's rule to convert from scattering strengths measured at 45 to 30 to be between 1 and 2 dB in magnitude and unbiased in sign. This estimate is based on measurements between 8 and 100 kHz [21], [24], [25]. Both MBES data sets confirm that there is hardly any correlation between scattering strength and grain size.…”
Section: A Comparison Of Measured With Literaturementioning
confidence: 55%
“…This issue could now be investigated using the wideband EK80 split-beam echosounder to generates fixed frequencies from 35 to 45 kHz thus giving a good estimate of frequency dependence in this range, in the same manner investigated for frequencies between 170 and 250 kHz by Weber and Ward (2015). Looking at the available literature, the dependency of backscatter level in this frequency band has been investigated (McKinney and Anderson 1964;Stanic et al 1988;Jackson et al 1986): results are highly variable and substrate dependent. Most studies agree on a dependency of BS with frequency f formulated as BS ∝ 10 log f x .…”
Section: Discussionmentioning
confidence: 99%
“…Another, and more likely cause, may lie within the dynamics of the skeletal structure. New bottom scattering model development: Initial measurements in 1960s (McKinney and Anderson 1964) and model studies, indicated that backscattering strength increased with frequency, and this was partially responsible for the frequency selection of the AN/SQQ-32 sonar. But later measurements did not uphold this trend.…”
Section: Approachmentioning
confidence: 99%